Physiological and Clinical Impact of Repeated Inhaled Oxygen Variation on Erythropoietin Levels in Patients After Surgery - Khalife, Maher; Ben Aziz, Mohammed; Balestra, Costantino; Valsamis, Joseph; Sosnowski, Maurice (Frontiers in Physiology, 2021)
The "Normobaric Oxygen Paradox" (NOP) is a physiologic mechanism that induces an increase of endogenous erythropoietin (EPO) production by creating a state of relative hypoxia in subjects previously exposed to hyperoxia, followed by a rapid return to normoxia. Oxygen exposure duration and inspired oxygen fraction required to observe a significant increase in EPO or hemoglobin are not clearly defined. Consequently, we here study the effect of one model of relative hypoxia on EPO, reticulocytes and hemoglobin stimulation in patients after surgery. Patients were prospectively randomized in two groups. The O2 group (n=10) received 100% oxygen for one hour per day for eight consecutive days, via a non-rebreathing mask. The control group (n=12) received no oxygen variation. Serum EPO, hemoglobin and reticulocyte count were measured on admission and postoperatively on days seven and nine. Percentage EPO at day nine with respect to the baseline value was significantly elevated within the groups (O2 group: 323.7SD ± 147.7; control group: 365.6 SD± 169.9) but not between them. No significant difference was found between the groups in terms of reticulocytes count and hemoglobin. Our NOP model showed no difference on EPO increase between the two groups. However, both groups expressed separately significant EPO elevation.